2009
DOI: 10.1111/j.1551-2916.2008.02871.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transformation and Tunable Piezoelectric Properties of Lead‐Free (Na0.52K0.48−xLix)(Nb1−xySbyTax)O3 System

Abstract: Lead-free (Na 0.52 K 0.48Àx )(Nb 1ÀxÀy Sb y )O 3 -xLiTaO 3 (NKNS-LT) piezoelectric ceramics have been fabricated by ordinary sintering. A special attention was paid to the composition design through which the dielectric and piezoelectric properties of the (Li, Ta, Sb) modified NKN systems were significantly promoted. A property spectrum was generated with a particular discussion on the relationship between the Sb content, the LT content, the polymorphic phase transition, and the electrical properties and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(110 citation statements)
references
References 13 publications
3
107
0
Order By: Relevance
“…The results of conventional mixed oxide reactions for these compositions reveal that Li + and Sb 5+ diffuse into the parent lattices to form a solid solution with a perovskite structure 31 , but this seems to reduce its orthorhombicity because of the coexistence of orthorhombic and tetragonal phases 14 . Also, the T c decreased gradually with increasing Sb content.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of conventional mixed oxide reactions for these compositions reveal that Li + and Sb 5+ diffuse into the parent lattices to form a solid solution with a perovskite structure 31 , but this seems to reduce its orthorhombicity because of the coexistence of orthorhombic and tetragonal phases 14 . Also, the T c decreased gradually with increasing Sb content.…”
Section: Resultsmentioning
confidence: 99%
“…However, several researchers have examined solid solution formation of related compositional series to the one presented here, involving different NKN-LT binary compositions and extending along the join to LiSbO 3 (Table 1) 14, 26-31 ; e.g., (1−x)[(K 0.5 Na 0.5 )(Nb 0.925 Ta 0.075 )O 3 ]-x LiSbO 3 with x between 0 and 0.1, and also (Na 0.52 K 0.48 − x Li x )(Nb 1 − x − y Sb y Ta x )O 3 (0 < x < 0.07, 0 < y < 0.16) 14,31 . The results of conventional mixed oxide reactions for these compositions reveal that Li + and Sb 5+ diffuse into the parent lattices to form a solid solution with a perovskite structure 31 , but this seems to reduce its orthorhombicity because of the coexistence of orthorhombic and tetragonal phases 14 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a compositionally optimized Li-doped composition, its piezoelectric coefficient d 33 can be increased up to 324 pC/N even from a considerably high value (190 pC/N) by means of re-poling treatment after room temperature aging; such a high d 33 value is only reachable in literature for KNN ceramics with complicated modifications using Ta and Sb dopants [46,98,99]. Table 2 shows the piezoelectric coefficient d 33 as well as tetragonal-orthorhombic phase transition temperature (T O-T ) of Li-doped KNN ceramics with respect to Li content, after both the first and second poling, respectively.…”
Section: Poling Tricksmentioning
confidence: 99%
“…These exceptional properties were achieved through a complex texturing process. In subsequent investigations it was demonstrated that KNN-based materials depict promising small [280][281][282][283] and large 136 signal properties with conventional solid state synthesis. However, this family of materials presents major synthesis difficulties that need to be overcome for entering a reliable large scale production.…”
Section: Literature Review: Piezoceramics For Actuator Applicationsmentioning
confidence: 99%